2005
DOI: 10.1002/chin.200515182
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclohexapeptides Containing Pro and Aib Residues.

Abstract: Cyclization reactions on hexapeptides containing several alpha-aminoisobutyric acid (= 2-amino-2-methylpropanoic acid; Aib) residues and the turn-promoting glycine (Gly) and proline (Pro) residues were investigated. Eight linear hexapeptides were synthesized, and their cyclization was attempted with various coupling reagents. The macrolactamization step proved to be difficult since only three hexapeptides could be cyclized. Two of these latter peptides were the linear precursors of the same cyclic hexapeptide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Next, the macrolactamisation ability of the organophosphorus reagent DEPC [35] was tested. This reagent showed high efficiency during the cyclisation of Aib-containing penta-and hexapeptides [12][13][14]18]. However, the cyclisation step leading to cyclic octapeptide 1 resulted only in a complex mixture of products.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, the macrolactamisation ability of the organophosphorus reagent DEPC [35] was tested. This reagent showed high efficiency during the cyclisation of Aib-containing penta-and hexapeptides [12][13][14]18]. However, the cyclisation step leading to cyclic octapeptide 1 resulted only in a complex mixture of products.…”
Section: Resultsmentioning
confidence: 99%
“…We are interested in the design and synthesis of cyclic peptides containing C(2)-tetrasubstituted αamino acids in order to achieve a greater degree of conformational rigidity in a cyclopeptide structure. Our previous successful synthesis of cyclic hexapeptides containing several Aib residues [12][13][14] prompted us to investigate the cyclisation tendencies of longer Aib-containing peptides. The cyclisation of peptides consisting of more than seven amino acid residues is generally considered easier to accomplish in comparison with the cyclisation of small linear peptides (three to six amino acids) [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wellknown example is alamethicin, [1][2][3][4][5] a membrane-channel forming peptaibol [6][7][8][9][10][11][12][13] with antibiotic activities. We have shown that the 'azirine/oxazolone method' [14][15][16][17][18] is a convenient approach for the synthesis of Aib-containing oligopeptides [15,[19][20][21][22][23][24] and peptaibols. [25][26][27][28][29][30][31][32] In addition to Aib, peptaibols may also contain the chiral α,α-disubstituted α-amino acid isovaline (Iva).…”
Section: Introductionmentioning
confidence: 99%